Impact of recipient's age on heart transplantation outcome - Tjang, Yanto Sandy; van der Heijden, Geert J M G; Tenderich, Gero; Körfer, Reiner; Grobbee, Diederick E (The Annals of thoracic surgery, 2008)
The shortage of donor hearts stimulates the debate whether heart transplantation is justified for older recipients. We studied the effect of recipient's age on heart transplantation outcome in a large cohort of recipients. Between March 1989 and December 2004, 1262 adult recipients underwent heart transplantation. Recipients were divided into two groups: 540 recipients aged younger than 55 years and 722 aged 55 years or older. The overall 30-day mortality risk was 9%, at 6% for recipients younger than 55, and 10% for recipients 55 years or older (p = 0.005). Rejection, multiorgan failure, infection, and right heart failure dominated the causes of early death in both groups. The 1-, 5-, 10-, and 15-year survival was 84%, 75%, 60%, and 50%, respectively, for recipients younger than 55 years, and 73%, 63%, 48%, and 35%, respectively, for recipients aged 55 years and older (p < 0.001). The mortality rate for those who survived the first month was 58/1000 patient-years. The main causes for late mortality were cardiac allograft vasculopathy, rejection, and infection for recipients younger than 55 years; and infection, malignancies, and rejection for recipients aged 55 years or older. Both the crude and adjusted hazard ratio increased with increasing recipient's age. The outcome of heart transplantation in older recipients is less favorable than in younger recipients. The decision to offer heart transplantation to recipients older than 55 years should be considered cautiously.